2015
DOI: 10.3389/fmicb.2015.01049
|View full text |Cite
|
Sign up to set email alerts
|

Choosing a suitable method for the identification of replication origins in microbial genomes

Abstract: As the replication of genomic DNA is arguably the most important task performed by a cell and given that it is controlled at the initiation stage, the events that occur at the replication origin play a central role in the cell cycle. Making sense of DNA replication origins is important for improving our capacity to study cellular processes and functions in the regulation of gene expression, genome integrity in much finer detail. Thus, clearly comprehending the positions and sequences of replication origins whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 191 publications
(225 reference statements)
0
16
0
Order By: Relevance
“…Another mutation method is flanking ARS‐seq, which keeps the core ACS unchanged and makes mutants flanking sequences form a mutant library, combining with sequence analysis. This method effectively selects the appropriate flanking sequences, and investigates the function of ACS flanking region [19, 73]. Through mutation, we can obtain high‐efficiency ARSs and simply verify its efficiency by measuring the conversion rate [30, 74].…”
Section: Ars Modificationsmentioning
confidence: 99%
“…Another mutation method is flanking ARS‐seq, which keeps the core ACS unchanged and makes mutants flanking sequences form a mutant library, combining with sequence analysis. This method effectively selects the appropriate flanking sequences, and investigates the function of ACS flanking region [19, 73]. Through mutation, we can obtain high‐efficiency ARSs and simply verify its efficiency by measuring the conversion rate [30, 74].…”
Section: Ars Modificationsmentioning
confidence: 99%
“…Several in vitro and in vivo experimental techniques, such as chromatin immunoprecipitation (ChIP), ChIP-sequencing, DNase I footprinting technique, electrophoretic mobility shift assays, gel retardation assay, isothermal titration calorimetry, replication initiation point mapping and surface plasmon resonance have been developed to identify DNA ORIs [ 5 ]. Lee and Bell [ 6 ] reported that the origin recognition complex (ORC) that binds ORIs could be accurately detected [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the processes of DNA replications are different for bacteria, archaea, and eukaryotes, they all share the same core components as elaborated in [12]. For in-depth understanding the genome duplication, it is important to find the “origin of replication region” (Ori), or “replication origin” (RO) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, it is quite natural to establish the replication forks at multiple locations [3] in order for timely duplicating their larger linear chromosomes. Therefore, to in-depth understand the process of cell reproduction, it is fundamentally important to acquire the RO information [1]. …”
Section: Introductionmentioning
confidence: 99%